2011
DOI: 10.1111/j.1365-2494.2011.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable, low‐input, warm‐season, grass–legume grassland mixtures: mission (nearly) impossible?

Abstract: Grazing lands in warm-temperate and subtropical North America have become less diverse. Pastures are typically grass monocultures, while rangelands are generally managed for the grass components. Overstocking, selective herbicides, fire exclusion and heavy rates of nitrogen fertilizer have contributed to near exclusion of native, warm-season legumes. The simplicity of managing grass monocultures, pasture production responses to nitrogen fertilizer and profitability of grass-only systems have limited interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 70 publications
(88 reference statements)
1
91
0
1
Order By: Relevance
“…This supports their potential value as forage sources during winter (Dall-Agnol and Gomes 1994;Coelho 1996). In a similar way, several native warm-temperate herbaceous legumes have been described in north-central Texas (USA) that can survive freezing temperatures during winter, with minor decreases to their nutritive value (Muir et al 2011).…”
Section: Introductionmentioning
confidence: 53%
“…This supports their potential value as forage sources during winter (Dall-Agnol and Gomes 1994;Coelho 1996). In a similar way, several native warm-temperate herbaceous legumes have been described in north-central Texas (USA) that can survive freezing temperatures during winter, with minor decreases to their nutritive value (Muir et al 2011).…”
Section: Introductionmentioning
confidence: 53%
“…Under West African conditions, construction of stone bunds and establishment of contour vegetative hedgerows can be effective for water conservation [95]. Establishment and management of forage trees (i.e., Acacia fadherbia) [96] and grass-legume mixtures [97] can also improve the quality of rangeland soils.…”
Section: Soil Restorative Farming/cropping Systemsmentioning
confidence: 99%
“…In addition, this cultivation system is a sustainable production strategy. Muir, Pitman, andFoster (2011), Azevedo Junior et al (2012), Lüscher, Mueller-Harvey, Soussana, Rees, andPeyraud (2014), McLeod, Banerjee, Bork, Hall, andHare (2015), and Vrignon-Brenas et al (2016) have all reported that the forage consortium system helps reduce the consumption of chemical fertilizers and pesticides. Multi-species crops also conserve and increase local biodiversity.…”
Section: Acta Scientiarum Animal Sciencesmentioning
confidence: 99%